Phosphatidylserine-targeting bis(zinc-dipicolylamine) farnesol inhibits ATP production in cancer cells to overcome multidrug resistance - Wei Huang; Xuan Nie; Xiao-Hong Zhou; Lei Qiao; Hong-Jie Gao; Jing Zang; Long-Kang Yu; Long-Hai Wang; Ye-Zi You (Supramolecular Materials)
Multidrug resistance significantly impedes the efficacy of cancer chemotherapy. Resistance often arises from the reduced cellular uptake of chemotherapeutic drugs, a process crucial for their cytotoxic effects. This reduction is frequently due to transmembrane efflux pumps powered by ATP from mitochondria and the cytoplasmic matrix, leading to lower intracellular concentrations of these drugs. This study introduces an amphiphilic molecule, bis(zinc-dipicolylamine) farnesol (Bis-ZnDPA), which targets phosphatidylserine (PS) – a negatively charged phospholipid prominently displayed on the outer leaflet of cancer cell plasma membranes. Integrating the hydrophobic segment of Bis-ZnDPA into the plasma membrane disrupts its integrity, potentially leading to hole formation and facilitating the uptake of chemotherapeutic drugs. Furthermore, the binding of Bis-ZnDPA to phosphatidylserine inhibits ATP production caused by Ca2+ influx and deregulation of the phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) signaling pathway, reducing the efflux of drugs from cells. The results indicate the potent synergistic effect of Bis-ZnDPA with chemotherapeutic agents, suggesting that targeting PS is a viable strategy for overcoming multidrug resistance in cancer chemotherapy.